Incidence of difficult airway situations during prehospital airway management by emergency physicians—A retrospective analysis of 692 consecutive patients. (May 2015) - Thoeni, Nils; Piegeler, Tobias; Brueesch, Martin; Sulser, Simon; Haas, Thorsten; Mueller, Stefan M.; Seifert, Burkhardt; Spahn, Donat R.; Ruetzler, Kurt
Abstract: Introduction: In the prehospital setting, advanced airway management is challenging as it is frequently affected by facial trauma, pharyngeal obstruction or limited access to the patient and/or the patient's airway. Therefore, incidence of prehospital difficult airway management is likely to be higher compared to the in-hospital setting and success rates of advanced airway management range between 80 and 99%. Methods: 3961 patients treated by an emergency physician in Zurich, Switzerland were included in this retrospective analysis in order to determine the incidence of a difficult airway along with potential circumstantial risk factors like gender, necessity of CPR, NACA score, GCS, use and type of muscle relaxant and use of hypnotic drugs. Results: 692 patients underwent advanced prehospital airway management. Seven patients were excluded due to incomplete or incongruent documentation, resulting in 685 patients included in the statistical analysis. Difficult intubation was recorded in 22 patients, representing an incidence of a difficult airway of 3.2%. Of these 22 patients, 15 patients were intubated successfully, whereas seven patients (1%) had to be ventilated with a bag valve mask during the whole procedure. Conclusion: In this physician-led service one out of five prehospital patients requires airway management. Incidence of advanced prehospital difficult airway management is 3.2% and eventual success rate is 99%, if performed by trained emergency physicians. A total of 1% of all prehospital intubation attempts failed and alternative airway device was necessary.